2010
DOI: 10.2114/jpa2.29.43
|View full text |Cite
|
Sign up to set email alerts
|

Daily Walking Activity among Male Office Workers in a Rural Town in Northern Japan

Abstract: To investigate the level of walking activity among residents of the Tohoku district in northern Japan, where no widespread public transport system has been developed, winter is severe. The participants were 50 town hall employees with an average age of 43.6Ϯ10.8 (SD) years. The walking activity of each participant was assessed using a pedometer for one week in summer and one week in winter. The participants' lifestyles, including their commuting methods, were assessed using a questionnaire. Forty-six participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…This result conflicts with the common belief that physical activity is more likely to be performed in leisure time than during working days. These results also differ from those of Mitsui et al [15] showing that office workers are more active on non-working days than on working days during summer, with an inverse pattern in the winter season. The authors suggest that the number of daily steps taken by participants in their study was not reduced on holidays, because they were not active on workdays, due to the fact that most of them were desk workers who commuted in private cars and some participants enjoyed walking or hiking on holiday [15].…”
Section: Discussioncontrasting
confidence: 99%
“…This result conflicts with the common belief that physical activity is more likely to be performed in leisure time than during working days. These results also differ from those of Mitsui et al [15] showing that office workers are more active on non-working days than on working days during summer, with an inverse pattern in the winter season. The authors suggest that the number of daily steps taken by participants in their study was not reduced on holidays, because they were not active on workdays, due to the fact that most of them were desk workers who commuted in private cars and some participants enjoyed walking or hiking on holiday [15].…”
Section: Discussioncontrasting
confidence: 99%
“…We also noted that the impact of access to treadmill desks on daily physical activity occurred regardless of seasonal effect although season impacted baseline activity (Spring activity levels were greater than Fall). Seasonal variance in daily physical activity is known to occur (32); the observation that the intervention impacted employees working indoors, regardless of seasonality, is noteworthy. The interindividual consistency of daily activity we found to be intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the existing evidence on walking (referred to as pedometer‐determined PA) has been presented by researchers from Western countries and Japan. Findings revealed that pedometer‐determined PA is inversely correlated with body mass index (BMI) in Canadian adults (Chan, Spangler, Valcour, & Tudor‐Locke, 2003), African‐American middle‐aged women (Hornbuckle, Bassett, & Thompson, 2005), American middle‐aged women (Thompson et al, 2004), and Japanese adults (Mitsui, Barajima, Kanachi, & Shimaoka, 2010; Mitsui, Shimaoka, Tsuzuku, Kajioka, & Sakakibara, 2008). A weak to moderate relationship has been reported.…”
mentioning
confidence: 99%